2018
DOI: 10.1002/cnma.201800192
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Optical and Self‐Assembly Properties of Diketopyrrolopyrrole Semicarbazone Derivatives through Hydrogen Bonding

Abstract: Hydrogen bonds are great noncovalent interactions for guiding self‐assembly processes in organic semiconductors. Their presence in molecular structures allows to modify their aggregation state by changing the solvent, concentration and temperature. Here we show that just by functionalizing simple thiophene‐capped diketopyrrolopyrrole derivatives with semicarbazone units, the optical and self‐assembly properties can be tuned while controlling the formation of hydrogen bonding. The appearance of J‐type aggregate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 45 publications
(69 reference statements)
6
20
0
Order By: Relevance
“…In this sense, the application of supramolecular chemistry strategies, in which noncovalent interactions form highly organized semiconducting structures could be very beneficial . Directional noncovalent interactions, such as hydrogen bonds (H‐bonds), can be introduced in the semiconducting segments and guide the self‐assembly towards different supramolecular structures with different optoelectronic properties . This is due to the high sensitivity of H‐bonds to external stimuli and their environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the application of supramolecular chemistry strategies, in which noncovalent interactions form highly organized semiconducting structures could be very beneficial . Directional noncovalent interactions, such as hydrogen bonds (H‐bonds), can be introduced in the semiconducting segments and guide the self‐assembly towards different supramolecular structures with different optoelectronic properties . This is due to the high sensitivity of H‐bonds to external stimuli and their environment.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic moieties are usually attached to the DPP core to tune the optoelectronic properties and they are normally modified with electron‐donating or withdrawing groups . The incorporation of H‐bonds also impacts the self‐assembly and optoelectronic properties of DPP derivatives without extending the conjugation length . Chirality has been introduced in DPP derivatives mainly by linking them to chiral alkyl tails, usually 2‐ethylhexyl, to helicene molecules, or adding myrtenal derivatives .…”
Section: Introductionmentioning
confidence: 99%
“…After gradual addition of methanol (MeOH), a hydrogen‐bond‐disrupting protic solvent, the absorption peak intensity at λ =636 nm decreased whereas the absorption intensity at λ =613 nm increased gradually (Figure S6 in the Supporting Information). This clearly indicated that the peak at λ =636 nm corresponds to hydrogen aggregation of NH‐TATDPP . In contrast Boc‐TATDPP exhibited no change in the absorption spectra in CHCl 3 even after addition of a large amount of MeOH, which therefore confirmed the important role of hydrogen bonding between the amide groups for the self‐assembly of NH‐TATDPP.…”
Section: Resultsmentioning
confidence: 67%
“…It has been previously reported that H-and J-aggregates can be differentiated for the DPP dyes based upon the ratio of 0-1/0-0 vibronic peaks, where a higher 0-1 peak indicates Haggregates, and a higher 0-0 peak is suggestive of J-aggregates. [59][60][61] By monitoring the change in this ratio during hydrolysis it was found that the ratio went from more than unity (t < 40 min) to less than unity (t > 40 min), suggesting that Jaggregates form upon biocatalytic hydrolysis and assembly. Comparative analysis of the UV-Vis spectra (Fig.…”
Section: Resultsmentioning
confidence: 99%